Robert Garrett family papers - Garrett, Robert, 1783-1857.; Garrett, Henry S. (Henry Stouffer), 1818-1867.; Garrett, John W. (John Work), 1820-1884.
Correspondence, business records, and other papers relating chiefly to the involvement of Robert Garrett and his sons, John W. Garrett and Henry S. Garrett, in mercantile affairs in Baltimore, Md. Focuses on the business of Robert Garrett & Sons in connection with its mercantile trade and banking house, ventures in transportation and communication, and wholesale grocery, produce, forwarding, and commission business; and on the Garret's administration of the Baltimore and Ohio Railroad Company. Documents the Garrett's dealings with George Peabody & Co. of London, England, and with commercial interests in New Orleans, La.; San Francisco, Calif.; Europe; and South America. Also includes material pertaining their promotion of the western trade of farmers through the port of Baltimore and of the establishment of wagon trains moving over the turnpikes across the Allegheny Mountains and connecting with Pennsylvania canals and rivers.
Subjects include financing of the Civil War, movement of Union troops and supplies, military arrest of Maryland citizens during the war, and efforts to free Confederate president Jefferson Davis following his capture by the Union; establishment of cable and telegraph lines; development of summer resorts in Garrett County, Md,; the financial panics of 1837 and 1857 and related government policy; the Mexican War; and John W. Garrett's involvement in national politics including his support of Abraham Lincoln. Subjects also include education of family members at Johns Hopkins University, Baltimore, Md.; Lafayette College, Easton, Pa.; Mount Holyoke Female Seminary, South Hadley, Mass.; Princeton University, Princeton, N.J.; and other institutions. Also includes material pertaining to the family's philanthropic interests such as the Baltimore and Ohio Employes Relief Association, the Young Men's Christian Associations of North America, Johns Hopkins Hospital, the Johns Hopkins University Peabody Institute, art museums, and other local charities.
Correspondents include J.J. Atkinson, Varina Davis, Wm. G. Harrison, John H.B. Latrobe, James McHenry, J. Pierpont Morgan, William Parker, George Peabody, Sir S. Morton Peto, Philip E. Thomas, and Robert Benson and Company. An appendix to the finding aid lists selected correspondents according to their profession, association, or office.
Garrett family of Baltimore, Md. Family members represented include Robert Garrett, railroad official, financier, and merchant, and his son John W. Garrett, railroad official and financier.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Atkinson, J. J. -- Correspondence; Davis, Jefferson, -- 1808-1889.; Davis, Varina, -- 1826-1906 -- Correspondence; Latrobe, John H. B. -- 1803-1891 -- Correspondence; McHenry, James, -- 1817-1891 -- Correspondence; Morgan, J. Pierpont -- 1837-1913 -- Correspondence; Parker, William, -- 1807-1868 -- Correspondence; Peabody, George, -- 1795-1869 -- Correspondence; Peto, S. Morton -- Sir, -- 1809-1889 -- Correspondence; Thomas, Philip E. -- 1776-1861 -- Correspondence; Garrett family; United States. -- Army -- History -- Civil War, 1861-1865.; Baltimore and Ohio Employes Relief Association; Baltimore and Ohio Railroad Company; George Peabody & Co; Johns Hopkins Hospital; Johns Hopkins University; Johns Hopkins University. -- Peabody Institute; Lafayette College (Easton, Northampton County, Pa.); Mount Holyoke Female Seminary; Princeton University; Robert Benson and Company -- Correspondence; Robert Garrett & Sons; Young Men's Christian Associations of North America; Art museums; Banks and banking -- Maryland -- Baltimore; Brokers -- Maryland -- Baltimore; Charities -- Maryland -- Baltimore; Commission merchants -- Maryland -- Baltimore; Farm produce -- Maryland; Financial crises -- United States -- 19th century; Grocery trade -- Maryland -- Baltimore; Harbors -- Maryland -- Baltimore; Mexican War, 1846-1848.; Martial law -- United States; Merchants -- Maryland -- Baltimore; Railroads -- United States; Summer resorts -- Maryland -- Garrett County; Telecommunication -- United States; Telegraph -- United States; Transportation -- United States; Wagon trains -- Maryland; Wagon trains -- Pennsylvania; Baltimore (Md.) -- Commerce; Baltimore (Md.) -- Commerce -- California -- San Francisco; Baltimore (Md.) -- Commerce -- England -- London; Baltimore (Md.) -- Commerce -- Europe; Baltimore (Md.) -- Commerce -- Louisiana -- New Orleans; Baltimore (Md.) -- Commerce -- South America; Europe -- Commerce -- Maryland -- Baltimore; London (England) -- Commerce -- South America; Maryland -- History -- Civil War, 1861-1865.; New Orleans (La.) -- Commerce -- Maryland -- Baltimore; San Francisco (Calif.) -- Commerce -- Maryland -- Baltimore; South America -- Commerce -- Maryland -- Baltimore; United States -- Economic conditions -- To 1865.; United States -- Economic policy -- To 1933.; United States -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Finance; United States -- Politics and government -- 19th century